The effects of work-rest duration on intermittent exercise and subsequent performance - Price, M.; Halabi, K. (Journal of Sports Sciences, 2005)
This study examined the effects of different work-rest durations during 40min intermittent treadmill exercise and subsequent running performance. Eight males (mean±s: age 24.3±2.0 years, body mass 79.4±7.0kg, height 1.77±0.05m) undertook intermittent exercise involving repeated sprints at 120% of the speed at which maximal oxygen uptake (v-VO2max) was attained with passive recovery between each one. The work-rest ratio was constant at 1:1.5 with trials involving short (6:9s), medium (12:18s) or long (24:36s) work-rest durations. Each trial was followed by a performance run to volitional exhaustion at 150% v-VO2max. After 40min, mean exercise intensity was greater during the long (68.4±9.3%) than the short work-rest trial (54.9±8.1%VO2max; P<0.05). Blood lactate concentration at 10?min was higher in the long and medium than in the short work?-?rest trial (6.1±0.8, 5.2±0.9, 4.5±1.3mmol·l-1, respectively; P<0.05). The respiratory exchange ratio was consistently higher during the long than during the medium and short work-rest trials (P<0.05). Plasma glucose concentration was higher in the long and medium than in the short work-rest trial after 40min of exercise (5.6±0.1, 6.6±0.2 and 5.3±?0.5mmol·l-1, respectively; P<0.05). No differences were observed between trials for performance time (72.7±14.9, 63.2±13.2, 57.6±13.5s for the short, medium and long work-rest trial, respectively; P=0.17), although a relationship between performance time and 40?min plasma glucose was observed (P<0.05). The results show that 40?min of intermittent exercise involving long and medium work-rest durations elicits greater physiological strain and carbohydrate utilization than the same amount of intermittent exercise undertaken with a short work-rest duration.